Parenthood and the gender division of labour across the income distribution: the relative importance of relative earnings. (21st October 2022) - Dunatchik, Allison
Abstract: This study employs a gendered relative resource approach to examine whether the importance of relative resources varies by couples' household income in shaping changes in the gender division of labour after first birth. Scholarship has long argued that the gender division of labour within different-sex couples is influenced by partners' relative resources. However, couples face class-based constraints that may alter the relevance of relative resources in shaping changes in gender divisions of labour following the transition to parenthood. This study compares couples' paid work and housework before and up to four years after first birth, using 28 waves of the British Household Panel Survey and the UK Household Longitudinal Study ( N = 1, 606 couples). I find that the effect of relative resources on changes in couple's paid work and housework behaviour after first birth varies substantially by household income. Among higher-income couples, women's paid work and housework time changes less among those with high relative earnings and more among those with low relative earnings, while men's time allocation varies little after first birth. In contrast, among low-income couples, women's paid work time and share decreases most after first among female breadwinners while their male partners' paid work time increases substantially. These findings reflect the greater constraints that low-income parents face in reconciling work and family and highlight the need for greater attention to class interactions in the process of gender specialization in both research and work-family policy.